INDUSTRY CONCENTRATION AND GROWTH IN PHILIPPINE AGRICULTURE - Karen Debbie Jabenar Cosrojas; Rec E Eguia (Socio-Economics/Agribusiness Department, 2021)
The study investigated the extent of relationship of the agriculture industry concentration and growth of Philippine agriculture. Specifically, it determined the key agriculture sub-sectors in each region in the Philippines and investigated the regional industry concentration and economic performance nexus. The objectives were achieved using secondary data for the 16 regions in the Philippines. Location Quotient (LQ) and correlation analysis were used as tools to make sense of the data. Results show a number of key industries in each region which from the assumptions of the LQ formed the economic base of the region. The findings show non-significant correlation between regional industry concentration and the GVA for agriculture. This suggested for further investigation of the concentration or diversity relationship to economic performance.